Recruitment of Antigen Presenting Cells to Skin Draining Lymph Node From HPV16E7-Expressing Skin Requires E7-Rb Interaction - Kuo, Paula; Teoh, Siok Min; Tuong, Zewen K.; Leggatt, Graham R.; Mattarollo, Stephen R.; Frazer, Ian H. (Frontiers in Immunology, 2018)
“High-risk” human papillomaviruses (HPV) infect keratinocytes of squamous epithelia. The HPV16E7 protein induces epithelial hyperplasia by binding Rb family proteins and disrupting cell cycle termination. Murine skin expressing HPV16E7 as a transgene from a keratin 14 promoter (K14.E7) demonstrates epithelial hyperplasia, dysfunctional antigen presenting cells, ineffective antigen presentation by keratinocytes, and production of immunoregulatory cytokines. Furthermore, grafted K14.E7 skin is not rejected from immunocompetent non-transgenic recipient animals. To establish the contributions of E7, of E7-Rb interaction and of epithelial hyperplasia to altered local skin immunity, K14.E7 skin was compared with skin from K14.E7 mice heterozygous for a mutant Rb unable to bind E7 (K14.E7xRbΔL/ΔL mice), that have normoplastic epithelium. Previously, we demonstrated that E7-speicfic T cells do not accumulate in K14.E7xRbΔL/ΔL skin grafts. Here, we further show that K14.E7xRbΔL/ΔL skin, like K14.E7 skin, is not rejected by immunocompetent non-transgenic animals. However, K14.E7xRbΔL/ΔL keratinocytes, unlike K14.E7 keratinocytes, are susceptible to E7 directed CTL-mediated lysis in vitro. There were fewer CD11b+ antigen presenting cells in skin draining lymph nodes from animals recipient of K14.E7xRbΔL/ΔL grafts, when compared with animals receiving K14.E7 grafts or K5mOVA grafts. We conclude that E7-Rb interaction and its associated epithelial hyperplasia partially contribute to the suppressive local immune responses in area affected by HV16E7 expression. Moreover, the reduced trafficking of E7-specific T cells to K14.E7xRbΔL/ΔL transgenic skin may be due to inadequate presentation of E7 antigen in skin draining lymph nodes.